53.5k views
9 votes
Find the following for the function f(x)= 3x2 + 4x - 3.

(a) f(0)
(e) -f(x)
(b) f(3)
(f) f(x + 2)
(c) f(-3)
(g) f(3x)
(d) f(-x)
(h) f(x + h)

User Chejaras
by
5.0k points

2 Answers

5 votes

Final answer:

To evaluate the various expressions for the function f(x) = 3x^2 + 4x - 3, we substitute the indicated values and simplify accordingly to find f(0), f(3), f(-3), f(-x), -f(x), f(x + 2), f(3x), and f(x + h).

Step-by-step explanation:

To answer this question, we will evaluate and transform the function f(x) = 3x2 + 4x - 3 according to the provided operations.

(a) To find f(0), substitute x with 0: f(0) = 3(0)2 + 4(0) - 3 = -3.

(b) To find f(3), substitute x with 3: f(3) = 3(3)2 + 4(3) - 3 = 27 + 12 - 3 = 36.

(c) To find f(-3), substitute x with -3: f(-3) = 3(-3)2 + 4(-3) - 3 = 27 - 12 - 3 = 12.

(d) To find f(-x), substitute x with -x: f(-x) = 3(-x)2 + 4(-x) - 3 = 3x2 - 4x - 3.

(e) To find -f(x), multiply the function by -1: -f(x) = -(3x2 + 4x - 3) = -3x2 - 4x + 3.

(f) To find f(x + 2), substitute x with (x + 2): f(x + 2) = 3(x + 2)2 + 4(x + 2) - 3.

(g) To find f(3x), substitute x with 3x: f(3x) = 3(3x)2 + 4(3x) - 3 = 27x2 + 12x - 3.

(h) To find f(x + h), substitute x with (x + h): f(x + h) = 3(x + h)2 + 4(x + h) - 3.

User Hao Wu
by
5.0k points
6 votes

Step-by-step explanation:

a. -3

e. -3x^2 -4x +3

b 27+12-3= 36

f. 3(x+2)^2 + 4(x+2) -3

c. 27-12-3= 12

g. 3(3x)^2 + 4(3x) -3

d. 3x^2 -4x -3

h. 3(x+h)^2 + 4(x+h) -3

User Kshitij Mittal
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.